Impact of lower-volume training on physical fitness adaptations in team sports players: a systematic review and meta-analysis - Clemente, Filipe Manuel (2025)
Background A small number of reviews have explored lower‑ versus higher‑volume training in non‑athletes, but the growing challenge of congested schedules in team sports highlights the need to synthesize evidence specific to team sport athletes. Thus, the objectives of this systematic review with meta‑analysis are twofold: (i) to summarize the primary physiological and physical fitness outcomes of lower‑volume versus higher‑volume training interventions in team sports players; and (ii) to compare the effects of lower‑volume training with higher, considering the training modalities used. Methods We conducted searches across key databases, including PubMed, Scopus, SPORTDiscus, and Web of Science. We included team sports players with at least a trained or developmental level, focusing on studies comparing different training volumes (lower vs higher) within the same research. Lower volume training was defined in comparison to another load, emphasizing smaller training volume in terms of repetitions, duration, or frequency. The studies had to examine key physical performance adaptations and use two‑arm or multi‑arm designs. Methodological assessments of the included studies were performed using the Rob2 and ROBINS‑I instruments, with evidence certainty evaluated through GRADE. Results The initial search yielded 5,188 records, with 17 articles deemed eligible for the review. There was a non significant trend favoring the higher‑volume training group over the lower‑volume group in resistance‑based training when considering all pooled physical fitness outcomes (effect size − 0.05, 95% CI − 0.19 to 0.09, p = 0.506, I2 = 0.0%). A meta‑analysis was not conducted for aerobic‑based training due to only two studies being available, with one showing that lower volume training improved maximal oxygen uptake by 3.8% compared to 1.3% for higher volume, while the other indicated that lower training volumes enhanced performance by 1.6% versus 0.8%. The evidence certainty for physical performance outcomes was very low. Conclusions In newly introduced resistance training, lower volumes—regardless of repetitions or frequency—can achieve similar fitness gains to higher volumes. More pronounced tapering also appears more effective for super compensation. However, the variability in study designs and training methods makes it difficult to establish a clear minimal dose. The main contribution of this review is mapping current research, providing a foundation for future studies and training optimization. Key Points • Lower‑volume resistance training—whether by halving the number of repetitions in sessions held at least twice a week or by reducing the training frequency by half—produces similar positive adaptations in the physical performance of team sport athletes compared to higher‑volume training. • In running‑based and mixed‑based training interventions, specifically in tapering strategies, reducing volume while maintaining intensity seems to yield a more favorable response than employing a higher volume. • In tapering strategies, particularly concerning training load in field settings, more pronounced reductions in volume seem to enhance supercompensation. However, caution is warranted in interpreting this evidence, as the observed tendency could not be confirmed through meta‑analytical approaches.